Current Predictive Indices and Nomograms To Enable Personalization of Radiation Therapy for Patients With Secondary Malignant Neoplasms of the Central Nervous System: A Review. Issue 5 (6th April 2018) - Gilbride, Lucas; Siker, Malika; Bovi, Joseph; Gore, Elizabeth; Schultz, Christopher; Hall, William A
Abstract: The proper treatment of brain metastases continues to be a challenge for oncologists given the variability of individual patients' prognoses and the variety of treatment options available to address brain metasteses. There have been efforts since the 1990s to develop prognostic indices and nomograms to help clinicians determine the best approach for individuals with secondary malignant neoplasms of the central nervous system. A literature search was performed to identify the existing prognostic tools published between January 1995 and January 2017. While there have been several reported indices, many are limited by the number of patients analyzed or lack of generalizability. The most robust prognostic tools available are the Disease Specific Graded Prognostic Assessment and the Barnholtz-Sloan nomogram, both of which have online tools available to help clinicians. While these tools are helpful in stratifying different patients' outcomes, they are limited by their retrospective nature and likely underestimate survival in the modern era, where there is a rapidly growing arsenal of systemic agents available to patients with metastatic disease.